The Effect of Income, Financial Attitudes, And Locus Control on The Behavior of Financial Management Employees of PT BINA BUMI BERKAT - Ilmia Rahmawati; Anita Handayani; Wasti Reviandani (Universitas Muhammadiyah Gresik, 2023)
The background in this study is that the problems that affect financial management behavior are that employees at PT Bina Bumi Berkat are still not able to manage their financial management behavior properly. This study aims to examine the influence of income, financial attitudes, and locus control on financial management behavior of PT Bina Bumi Berkat employees. This research uses quantitative methods. The population in this study was PT Bina Bumi Berkat employees, totaling 120 people, while the sample was taken using the Non Probability Sampling technique using a saturated sample. the sample in this study is 120 permanent employees of PT Bina Bumi Berkati. The analysis technique uses instrument test, classic assumption test, and hypothesis test. For test aids using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that income has a positive and significant effect on the financial management behavior of PT Bina Bumi Berkat, financial attitudes have a positive and significant effect on the financial management behavior of PT Bina Bumi Berkat, and Locus Control has a positive and significant effect on the financial management behavior of PT Bina Bumi Berkat. .